The Activation of the Title III of the Helms-Burton Act: The Making of a Policy - Ernesto Domínguez López; Ariadna Cornelio Hitchman; Seida Barrera Rodríguez (International Journal of Cuban Studies)
The article addresses the early implementation of Title III of the Helms-Burton Act. We discuss the decision to activate the Title from the perspective of policymaking. We examine the behaviour of the key variables: the domestic variables and contextual variables, within the framework created by the structural variables in the form of state policy. We then address the lawsuits filed under Title III between May 2019 and January 2023 to identify the companies sued and the state of the processes as of January 2023. The low figures, underwhelming results for the defendants and technical issues with the texts filed, along with targeted companies, show the contradiction between the statute and the constitutional framework. The research also shows how those contradictions affect the rulings of the courts. We found evidence of the political dimension of the suits and their developments, and how it adds to the obstacles for any potential future rapprochement between the US and Cuba.